Pengaruh Budaya Organisasi dan Manajemen Pengetahuan terhadap Kinerja Karyawan di Bank Sinarmas Cabang Maumere (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to determine the effect of organizational culture on employee performance at Bank Sinarmas Maumere Branch, to determine the effect of knowledge management on employee performance at Bank Sinarmas Maumere Branch, and to determine the effect of organizational culture and knowledge management on employee performance at Bank Sinarmas Maumere Branch. The method used is descriptive statistical quantitative. The population and sample consisted of all 14 employees. Data analysis techniques used a checklist questionnaire. Variables were measured using a Likert scale. Data were analyzed using data quality tests and classical assumption tests, statistical hypothesis tests consisting of t-tests and F-tests, and multiple linear regression analysis. The results of this study indicate that organizational culture has a significant effect on employee performance, with a significance value of 0.000 (<0.05), showing that the better the organizational culture implemented, the higher the performance shown by employees. Knowledge management has a significant effect on employee performance, with a significance value of 0.032 (<0.05), indicating that effective knowledge management systems, such as regular training, knowledge documentation, and information sharing practices among employees, can improve work capabilities and the quality of individual performance. Organizational culture and knowledge management have a simultaneous influence on employee performance, indicating that a combination of positive organizational values and good knowledge management can create a productive and adaptive work environment.